MiR‐106b‐5p promotes aggressive progression of hepatocellular carcinoma via targeting RUNX3. (10th September 2019) - Gu, Hao; Gu, Shensen; Zhang, Xinlong; Zhang, Songjiang; Zhang, Dongming; Lin, Junsheng; Hasengbayi, Saiken; Han, Wei
Abstract: Background and Objectives: The roles of microRNA(miR)‐106b‐5p in hepatocellular carcinoma (HCC) remain unclear. We aimed here to investigate the clinical significance of miR‐106b‐5p expression in HCC and its underlying mechanisms. Methods: Expression levels of miR‐106b‐5p in 108 HCC clinical samples by quantitative real‐time reverse transcription PCR. Associations of miR‐106b‐5p expression with various clinicopathological features and patients' prognosis were evaluated by Chi‐square test, Kaplan‐Meier, and Cox proportional regression analyses, respectively. The target gene of miR‐106b‐5p and their functions in HCC cells were investigated by luciferase reporter, CCK‐8, and Transwell Matrigel invasion assays. Results: miR‐106b‐5p expression was markedly higher in HCC tissues than in noncancerous adjacent liver tissues ( P < .001). miR‐106b‐5p upregulation was significantly associated with advanced TNM stage ( P = .02), short recurrence‐free ( P = .005), and overall ( P = .001) survivals. Importantly, miR‐106b‐5p expression was an independent predictor of poor prognosis ( P < .05). RUNX3 was identified as a direct target gene of miR‐106b‐5p in HCC cells. Functionally, miR‐106b‐5p upregulation promoted the viability and invasion of HCC cells, while enforced RUNX3 expression reversed the oncogenic effects of miR‐106b‐5p overexpression. Conclusions: miR‐106b‐5p may serve as a potent prognostic marker for tumor recurrence and survival of HCC patients. miR‐106b‐5p may exert an oncogenic role in HCC via regulating its target gene RUNX3. Abstract : This study revealed the overexpression of miR‐106b‐5p in HCC tissues, which was dramatically associated with advanced cancer progression and unfavorable patients' prognosis. Functionally, miR‐106b‐5p upregulation promoted the viability and invasion of HCC cells, at least in part, by inhibiting its target gene RUNX3